The Airwaves in Arabia: BBC Arabic, British Imperialism, and the Arabian Peninsula’s Global Listenership, c. 1933-1940 - Gabriel Lavin (Arabian Humanities)
This article explores how the reception of early Arabic radio broadcasts throughout the Arabian Peninsula was connected to global media markets and geopolitics leading up to the Second World War. Specifically, it uses British efforts to establish the BBC Arabic service to investigate the various radio stations and other technologies that defined the region’s global media landscape during the 1930s. It argues that, while the BBC broadcasts pushed colonial territories in Arabian Peninsula away from British India into the fold of Britain's Middle East administration, colonial officials had to acknowledge Arabia’s social, economic, and cultural ties to the Indian Ocean region in order to have the BBC successfully compete with German and Italian broadcasts among Arab and Muslim audiences worldwide. As such, the article also suggests that the Arabian Peninsula’s role in the history of early Arabic broadcasting is significantly more important than previously assumed in scholarship.